# System of Linear Equations: Substitution Method

How to solve system of linear equations problems by using the substitution method: example and its solutions. (2 ways)

## Example

Choose one of the equations

and change it to '*x* = ' or '*y* = '.

Let's choose *x* - *y* = 4

and change it to *x* = *y* + 4.

Put *y* + 4 into the other equation's *x*.

Then *y* = -1.

Put *y* = -1 into *x* = *y* + 4.

Then *x* = 3.

So the answer is *x* = 3, *y* = -1.

## Example: Another Solution

Let's solve the same example

by choosing the other equation.

Let's choose 2*x* + *y* = 5

and change it to *y* = -2*x* + 5.

Put -2*x* + 5 into the other equation's *y*.

Then *x* = 3.

Put *x* = 3 into *y* = -2*x* + 5.

Then *y* = -1.

So the answer is *x* = 3, *y* = -1.

As you can see, you got the same answer.